Intervenção baseada em mindfulness e psicoeducação para mulheres com histórico de violência pelo parceiro íntimo - Dantas, Amanda Soares (Universidade Federal de São Carlos, 2020)
The literature in the area of intimate partner violence (IPV) indicates that women who have experienced violence are more likely to develop psychological disorders such as depression and anxiety. In addition, risk factors present in the community and society contribute to the perpetuation and re-victimization of women. Thus, an intervention for this population needs to take into consideration an educational and therapeutic perspective. Interventions using psychoeducation about IPV and mindfulness meditation have shown promising results to deal with the effects of IPV and, at the same time, teach skills such as acceptance of difficult feelings and non-judgmental contemplation of the present moment. This paper aimed to evaluate the feasibility of an individual intervention program in women with a history of IPV. Four participants with a history of IPV were recruited to participate in this study. One of them did not complete the intervention. Twelve individual sessions of about one hour divided into two modules were conducted: psychoeducation (4 sessions) and mindfulness (8 sessions). Assessments of depression and anxiety symptoms, with the Beck scales (BDI-II and BAI), as well as of mindfulness components (acceptance and awareness) were conducted at different moments of the intervention. To check whether the changes were clinically significant, the JT Method was used. The data indicated a decrease in depression and anxiety symptoms over the sessions, but clinically significant change only for anxiety symptoms. Analysis of the sessions indicated that the content addressed by the participants concerned their own history of violence, perceptions about meditating, and feedback from the intervention. It is discussed that this intervention model appears to be feasible, however further studies are needed.
Mindfulness and psychoeducation to IPV women survivors
Keywords: violência; psicoeducação; psychoeducation; mindfulness violence; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO